The Role Of Green Innovation And Environmental Leadership On The Performance Of Wooden Furniture Companies In Malaysia - Hamidi @ Abdul Rani, Muhammad Faisal (2019)
The present study is designed to investigate the organizational performance of the wooden furniture manufacturers in Malaysia using the theory of resources basedview and strategy innovation theory. The 650 respondents of this study were chosen from the list of wooden furniture manufacturers which are registered with Malaysia Furniture Promotion Council (MFPC) under wooden furniture manufacturer category.